Relationship between Arbitrability and Invalidity of the Arbitration Agreement - Varapnickas, Tadas; Zemlytė, Eglė (Teisė, 2026)
The article focuses on the relationship between arbitrability and the substantive validity of the arbitration agreement. It is justified that a dispute’s (non-)arbitrability is not a homogeneous notion. In some instances, it refers to an exceptionally procedural obstacle to deciding the dispute in arbitration, while, in other cases, it refers to a situation in which the dispute cannot be resolved in arbitration due to the invalidity of the arbitration agreement. The paper also analyses the notion of ‘conditional arbitrability’, when the possibility to decide a dispute in arbitration depends on the fulfilment of a condition relating to the arbitration agreement.
Keywords: arbitration; arbitrability; arbitration agreement; invalidity